Kualitas Hidup Penderita Kusta - Adiratna Sekar Siwi; Rohayanih Rohayanih (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Introduction. Leprosy is an infectious disease caused by Mycobacterium leprae that first attacks the peripheral nerve system, skin, mucosa (mouth), upper respiratory tract, endothelial reticulo system, eyes, muscle, bone and testes. Psychosocial problems arising in leprosy patients are more prominent than the medical problem itself because of the stigma and leprophobia influenced by misinformation about leprosy. Leprosy patients tend to close themselves, reduce social activities, feel depressed and ashamed for treatment so that it will affect the life quality level. Objective. To desribe the quality of life of leprosy outpatients.Method. The research used descriptive with cross sectional survey design. There were 45 respondents of leprosy patients in outpatient departements invited. A total sampling technique was applied from from leprosy data registers. WHOQOL-BREF questionnaire was utilized to measure the quality of life.Results. Most leprosy patients in Purbalingga District are 46-60 years old, male, elementary school graduation, 0 (zero) level defect, and good quality of life. Conclusion. The leprosy patients’s quality of life were good.